Dopuszczalność ulepszania natury ludzkiej (enhancement) - Holocher, Justyna; Kosielińska-Grabowska, Urszula (ETHICS IN PROGRESS, 2015)
The paper presents moral and legal aspects of the human’s nature enhancement in the context of answering the questions to what extent and to whom the modern technologies may be applied, which purpose is not the recovery (therapy), but the improvement of natural human potential by increasing the strength, endurance, immunity, physical fitness and human’s ability to regenerate, as well as by improving the cognitive capacities in the form of the betterment of human thinking and memory. The problems of enhancement are associated with the movement of transhumanism, which postulates the perfecting of a man and assumes the possibility to control more and more the domains of human activities, both physical and intellectual. In finding the answer to the question of the limits of moral acceptance for the enhancement of human nature, we analyze the cases of a soldier and sportsman, which illustrate the most important problems of the issue. The choice of such examples was due to the belief that social function and the types of activity connected with the exercise of these professions are very important for the determination of the acceptable limits of human enhancement. In our opinion the determination of the limit should be made by referring to the types of activity, based on the division of human activities elaborated by A. MacIntyre. According to MacIntyre, in the case of human activities known as practices, a man achieves internal goods, which define the practice and can only be achieved by improving human skills/abilities. While the external goods, like fame, money or prestige, do not belong to the essence of a practice. For these goods can be achieved both through honest work and self-improvement, and by the fraud. After considering a number of theoretical and practical problems, we argue for the thesis that the admissibility of artificial enhancements and the establishment of its acceptable limits are to be resolved by determining whether a given activity is oriented to achieve essential goods, like life, health or national security, which constitute the moral or social good (in such cases the use of enhancements sometimes will be even a duty), or this activity merely consist in the practice of virtues for the moral improvement of man, which should be made exclusively by using the natural human potential. Thus, the limit of the morally acceptable enhancement of the human nature is to be Dopuszczalność ulepszania natury ludzkiej (enhancement determined (at the stages of law-making and law-application) by indicating the nature of a given activity, its social function and importance, and therefore its moral or social significance.